SNP-based genetic linkage map of tobacco (Nicotiana tabacum L.) using next-generation RAD sequencing. Issue 1 (December 2015) - Xiao, Bingguang; Tan, Yuntao; Long, Ni; Chen, Xuejun; Tong, Zhijun; Dong, Yang; Li, Yongping
Abstract Background Tobacco (Nicotiana tabacum L.) is an important model system, which has been widely used in plant physiological studies and it is particularly useful as a bioreactor. Despite its importance, only limited molecular marker resources are available for genome analysis, genetic mapping and breeding. Restriction-site associated DNA sequencing (RAD-seq) is a powerful new method for targeted sequencing across the genomes of many individuals. This approach has broad potential for genetic analysis through linkage mapping. Results We constructed a RAD library using genomic DNA from a BC1 backcross population. Sequencing of 196 individuals was performed on an Illumina HiSeq 2500. Two linkage maps were constructed, one with a reference genome and another, termed as de novo identification of single nucleotide polymorphism (SNP) by RAD-seq, without a reference genome. Overall, 4138 and 2162 SNP markers with a total length of 1944.74 and 2000.9 cM were mapped to 24 linkage groups in the genetic maps based on reference genome and without reference, respectively. Conclusions Using two different SNP discovery methods based on next generation RAD sequencing technology, we have respectively mapped 2162 and 4318 SNPs in our backcross population. This study gives an excellent example for high density linkage map construction, irrespective of genome sequence availability, and provides saturated information for downstream genetic investigations such as quantitative trait locus analyses or genomic selection (e.g. bioreactor suitable cultivars).